AUGMENTATION THERAPY IN UNIPOLAR DEPRESSION WITH SUICIDAL BEHAVIOR WITH LITHIUM (EVIDENCE BASED CASE REPORT ) - Syarifah Husna; Yusvick M Hadin; Adriesti Herdaetha; Setyowati Raharjo (Departemen Psikiatri Fakultas Kedokteran Universitas Brawijaya, 2020)
Depressive disorder is the main cause associated with recurrent morbidity which is often associated with suicides. Treatment of depression with antidepressant and electroconvulsive therapy is commonly used and proven effective. Based on previous study, administration of lithium as an augmentation therapy showed efficacy in suicidal behavior. The role of lithium as first line for bipolar disorder in manic episodes, also be an option in unipolar depression with some conditions such as antidepressant resistence, recurrent depression, maintenance therapy which is respond to electroconvulsive therapy and suicide behavioral. Methode : The authors conducted an extensive search of the published literature using several terms, including major depressive, lithium, antidepressant and antisuicidal effects. Relevan article were retrieved from PubMed, Cochrane, Springer, ScinceDirect. Conclusion: Lithium given along antidepressants has proven effective in treatment of unipolar depression, preventing relaps and also has anti-suicide effect.